Neurotrophin gene augmentation by electrotransfer to improve cochlear implant hearing outcomes - Pinyon, Jeremy L.; von Jonquieres, Georg; Crawford, Edward N.; Duxbury, Mayryl; Al Abed, Amr; Lovell, Nigel H.; Klugmann, Matthias; Wise, Andrew K.; Fallon, James B.; Shepherd, Robert K.; Birman, Catherine S.; Lai, Waikong; et al. (Hearing research, 2019)
This Review outlines the development of DNA-based therapeutics for treatment of hearing loss, and in particular, considers the potential to utilize the properties of recombinant neurotrophins to improve cochlear auditory (spiral ganglion) neuron survival and repair. This potential to reduce spiral ganglion neuron death and indeed re-grow the auditory nerve fibres has been the subject of considerable pre-clinical evaluation over decades with the view of improving the neural interface with cochlear implants. This provides the context for discussion about the development of a novel means of using cochlear implant electrode arrays for gene electrotransfer. Mesenchymal cells which line the cochlear perilymphatic compartment can be selectively transfected with (naked) plasmid DNA using array - based gene electrotransfer, termed ‘close-field electroporation’. This technology is able to drive expression of brain derived neurotrophic factor (BDNF) in the deafened guinea pig model, causing re-growth of the spiral ganglion peripheral neurites towards the mesenchymla cells, and hence into close proximity with cochlear implant electrodes within scala tympani. This was associated with functional enhancement of the cochlear implant neural interface (lower neural recruitment thresholds and expanded dynamic range, measured using electrically - evoked auditory brainstem responses). The basis for the efficiency of close-field electroporation arises from the compression of the electric field in proximity to the ganged cochlear implant electrodes. The regions close to the array with highest field strength corresponded closely to the distribution of bioreporter cells (adherent human embryonic kidney (HEK293)) expressing green fluorescent reporter protein (GFP) following gene electrotransfer. The optimization of the gene electrotransfer parameters using this cell-based model correlated closely with in vitro and in vivo cochlear gene delivery outcomes. The migration of the cochlear implant electrode array-based gene electrotransfer platform towards a clinical trial for neurotrophin-based enhancement of cochlear implants is supported by availability of a novel regulatory compliant mini-plasmid DNA backbone (pFAR4; plasmid Free of Antibiotic Resistance v.4) which could be used to package a ‘humanized’ neurotrophin expression cassette. A reporter cassette packaged into pFAR4 produced prominent GFP expression in the guinea pig basal turn perilymphatic scalae. More broadly, close-field gene electrotransfer may lend itself to a spectrum of potential DNA therapeutics applications benefitting from titratable, localised, delivery of naked DNA, for gene augmentation, targeted gene regulation, or gene substitution strategies. •Cochlear mesenchymal cells can be targeted for gene electrotransfer via electric field compression using cochlear implants.•Regeneration of cochlear peripheral neurites after neurotrophin gene augmentation via bionic array-based electrotransfer.•Local recombinant neurotrophin expression enhances neural recruitment and electrically evoked auditory brainstem responses.•Bionic array directed gene electrotransfer requires low voltages albeit higher than existing cochlear implant capabilities.•Regulatory-permissive mini-plasmids free of antibiotic resistance genes achieve efficient gene expression in the cochlea.